The analysis of social singularity in the digital era: A socio-philosophical aspect - Utiuzh, I. H.; Konovalenko, O.; Volkova, V.; Утюж, Ірина Геннадіївна (My University, 2025)
Abstract: This article examines one of the most complicated issues of social research, namely social singularity as a process of producing unpredictable meanings, both in the life of modern society and an individual. The essence of social singularity is generally interpreted in the context of the coevolution of nature and society in the conditions of rapid technological shifts and changes in the role of the information environment. Therefore, this study aims to define and analyze the methodological tools of cognition of the social singularity phenomenon as a structural part of the new digital paradigm of philosophical discourse. The article considers the methodological approaches of various schools of philosophy represented by opposing views on anthropological reality in the context of its digital transformation.Within the framework of methodological structuring, the degree of the social singularity issue elaboration can be represented by the methodologies of postmodern and post-humanism philosophy. The conceptual approaches to the criticism of computational thinking, which forms the phenomenon of singularity eliminating the Human, are presented in the works by Baudrillard, Deleuze, Massumi, and Haraway. The article emphasizes that the papers of these scholars study digital ontology of the post-human state, where the boundaries between man and machine are blurred. Those studies include the analysis of cyber and biotechnological changes that affect human nature and create the concept of social singularity as a negative scenario for the development of the Human. Analyzing the phenomenon of social singularity, we emphasize that non-objectified human feelings come into conflict with computational thinking, since subjectivity, carried beyond the limits of the Self, turns into the non-human Other. Therefore, the article raises the question of how algorithms and artificial intelligence affect human subjectivity and free will; hence, the understanding of how computational processes can limit or expand human capabilitiesare of crucial importance.
Keywords: social singularity; digital ontology; computational thinking; consciousness; free will